Afterburn [videorecording (Blu-Ray)] - Johnson, Matt (Screenwriter); Antal, Nimród, 1973-; Bautista, David, 1969-; Kurylenko, Olga, 1979-; Hivju, Kristofer, 1978-; Jackson, Samuel L.; Baños, Roque; Wolfe, David (Costume designer); Montero, José David; Chitwood, Scott (Ketchup Entertainment, 2026)
After a massive solar flare destroys the Earth's Eastern Hemisphere, an emboldened treasure hunter for hire adventures to Europe to uncover the coveted Mona Lisa, only to learn the world needs a hero more than it needs a painting.